2010
DOI: 10.1021/ic101237c
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Ziegler-Type Hydrogenation Catalysts Made from [(1,5-COD)Ir(μ-O2C8H15)]2 and AlEt3: Spectroscopic and Kinetic Evidence for the Irn Species Present and for Nanoparticles as the Fastest Catalyst

Abstract: Ziegler-type hydrogenation catalysts, those made from a group 8-10 transition metal precatalyst and an AlR(3) cocatalyst, are often used for large scale industrial polymer hydrogenation; note that Ziegler-type hydrogenation catalysts are not the same as Ziegler-Natta polymerization catalysts. A review of prior studies of Ziegler-type hydrogenation catalysts (Alley et al. J. Mol. Catal. A: Chem. 2010, 315, 1-27) reveals that a approximately 50 year old problem is identifying the metal species present before, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(93 citation statements)
references
References 105 publications
5
88
0
Order By: Relevance
“…In view of the importance of triosmium and triruthenium clusters, we have studied its reactivity with heterocyclic phosphines known as phospholes, such as 1-phenylphosphole, 3,4dimethyl-1-phenylphosphole and 3-methyl-1-phenylphosphole [18][19][20]. Herein, we report the reaction between the unsaturated cluster [Os 3 (µ-H) 2 In general, we have found that the binding mode of the -conjugated phospholes in the unsaturated [Os 3 (µ-H) 2 (CO) 10 ] cluster is restricted to the two-electron typical coordination of a tertiary phosphine, where electronic properties and steric effects of these phospholes must be playing a role in controlling the final product distribution. whereas the minor isomer contains two equivalent phosphines ( Figure 3).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the importance of triosmium and triruthenium clusters, we have studied its reactivity with heterocyclic phosphines known as phospholes, such as 1-phenylphosphole, 3,4dimethyl-1-phenylphosphole and 3-methyl-1-phenylphosphole [18][19][20]. Herein, we report the reaction between the unsaturated cluster [Os 3 (µ-H) 2 In general, we have found that the binding mode of the -conjugated phospholes in the unsaturated [Os 3 (µ-H) 2 (CO) 10 ] cluster is restricted to the two-electron typical coordination of a tertiary phosphine, where electronic properties and steric effects of these phospholes must be playing a role in controlling the final product distribution. whereas the minor isomer contains two equivalent phosphines ( Figure 3).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Studies of electronic and coordinative deficiency in mononuclear complexes suggest that unsaturated transition metal clusters should exhibit unique patterns of chemical behavior with potential applications in catalysis [1][2][3][4][5]. The availability of multiple metallic binding sites at the heart of the cluster-surface can be an important factor influencing catalytic activity, occupying a position between traditional heterogeneous and homogeneous systems [6].…”
Section: Introductionmentioning
confidence: 99%
“…Carbonyl complexes that incorporate two or more metal centers are particularly attractive because of their ability to provide access to catalytic reaction pathways that might not be offered in mononuclear chemistry [25][26][27][28][29][30], such as reversible metal-metal bond cleavage, skeletal rearrangement without degradation and ligand activation via multisite coordination [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the synthesis and characterization of iridium clusters protected by a typical alkyne, phenylacetylene (PA), is reported. Recently, nanoparticles and clusters of Ir have attracted significant attention as active, selective catalysts for various reactions, e.g., CO 2 fixation, hydrogenation, and aerobic oxidation. In these studies, Ir nanoparticles and clusters were synthesized using ligands (thiols, phosphines), polymers (polyvinylpyrrolidone (PVP), dendrimers), and surfactants (ethylene glycol (EG)) as stabilizers or zeolites as support. Examples of atomically precise synthesis are limited to Ir 4 , Ir 6 , and Ir 9 . Motivated by the successful synthesis of Au analogues, e.g., Au 34 (PA) 16 and Au 54 (PA) 26 , PA-protected Ir clusters (Ir:PA) were synthesized via the ligation of PA to the preformed Ir clusters stabilized by EG.…”
Section: Introductionmentioning
confidence: 99%
“…(ethylene glycol (EG)) as stabilizers or zeolites as support. Examples of atomically precise synthesis are limited to Ir 4 , Ir 6 , and Ir 9 .23−25 Motivated by the successful synthesis of Au analogues, e.g., Au 34 (PA)16 and Au 54 (PA) 26 , 1−3 PA-protected Ir clusters (Ir:PA) were synthesized via the ligation of PA to the preformed Ir clusters stabilized by EG. The structures of Ir:PA clusters thus prepared, including core size, atom packing structure, and interfacial structure, were investigated by means of a wide variety of spectroscopic methods.…”
mentioning
confidence: 99%